Retail lending in Russia: the need and directions of digital transformation - N. Kazarenkova; E. Belyaeva (Вестник Северо-Кавказского федерального университета)
The financial sphere of activity is the most susceptible to digitalization processes, therefore, the level of technological effectiveness in the development of banking products and services is one of the main factors in the competitiveness of any commercial bank. In this regard, the development and introduction of digital innovations in the bank’s activities is one of the main tasks of the strategic development of the banking business. The sensitivity of retail customers to improving the banking system determines the importance and need for digital transformation of lending to the population in modern conditions. At the same time, retail lending represents a significant share of banking assets and is one of the promising areas of development of the banking business. Digitalization of retail lending services will increase the quality and efficiency of lending to the population in Russian banks.